Effect of Etazolate upon Cuprizone-induced Demyelination In Vivo: Behavioral and Myelin Gene Analysis. (10th February 2021) - Carrete, Alex; Padilla-Ferrer, Aïda; Simon, Anne; Meffre, Delphine; Jafarian-Tehrani, Mehrnaz
Highlights: Cuprizone affects inflammatory and myelin gene expression in vivo. Treatment with etazolate does not restore the level of gene expression upon demyelination. Spatial memory evaluated by Y-maze is not affected by cuprizone and/or etazolate treatment. Etazolate improves locomotor function following demyelination. Abstract: Demyelination is a well-known pathological process in CNS disorders such as multiple sclerosis (MS). It provokes progressive axonal degeneration and functional impairments and no efficient therapy is presently available to combat such insults. Recently, we have shown that etazolate, a pyrazolopyridine compound and an α-secretase activator, was able to promote myelin protection and remyelination after cuprizone (CPZ)-induced acute demyelination in C57Bl/6 mice. In continuation of this work, here we have further investigated the effects of etazolate treatment after acute cuprizone-induced demyelination at the molecular level (expression of myelin genes Plp, Mbp and Mag and inflammatory markers Il-1β, Tnf-α ) and at the functional level (locomotor and spatial memory skills) in vivo . To this end, we have employed two protocols which consists of administering etazolate (10 mg/kg/d) for a period of 2 weeks either during (Protocol #1) or after (Protocol #2) 5-weeks of CPZ-induced demyelination. At the molecular level, we observed that CPZ intoxication altered inflammatory and myelin gene expression and it was not restored with either of the etazolate treatment protocols. At the functional level, the locomotor activity was impaired after 3-weeks of CPZ intoxication (Protocol #1) and our data indicates a modest but beneficial effect of etazolate treatment. Spatial memory evaluated was not affected either by CPZ intake or etazolate treatment in both protocols. Altogether, this study shows that the beneficial effect of etazolate upon demyelination does not occur at the gene expression level at the time points studied. Furthermore, our results also highlight the difficulty in revealing functional sequelae following CPZ intoxication.